2012
DOI: 10.1080/15299732.2012.664967
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and Psychosis in Dissociative Identity Disorder and Schizophrenia

Abstract: Dissociative symptoms, first-rank symptoms of schizophrenia, and delusions were assessed in 40 schizophrenia patients and 40 dissociative identity disorder (DID) patients with the Multidimensional Inventory of Dissociation (MID). Schizophrenia patients were diagnosed with the Structured Clinical Interview for the DSM-IV Axis I Disorders; DID patients were diagnosed with the Structured Clinical Interview for DSM-IV Dissociative Disorders-Revised. DID patients obtained significantly (a) higher dissociation score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 23 publications
2
48
1
Order By: Relevance
“…Within logistic regression analysis Dorahy et al (2009) found that five voice-related dependent variables (hearing two or more voices, being told what to do by voices, feeling controlled by voices, voice content relating to someone influential in your life and voices replaying past memories) were significantly predicted by the DES-T in voice-hearers with either a schizophrenia or DID diagnoses. In contrast to the significant differences found between schizophrenia and DID groups by Dorahy et al (2009) and Laddis and Dell (2012), Honig et al (1998) found no significant differences between schizophrenia and DID groups regarding voice characteristics. A potential explanation for the differing results found between studies may be that small sample sizes were used, consequently limiting the statistical power in order to detect differences between variables.…”
Section: Dissociative Identity Disorder (Did)contrasting
confidence: 82%
See 3 more Smart Citations
“…Within logistic regression analysis Dorahy et al (2009) found that five voice-related dependent variables (hearing two or more voices, being told what to do by voices, feeling controlled by voices, voice content relating to someone influential in your life and voices replaying past memories) were significantly predicted by the DES-T in voice-hearers with either a schizophrenia or DID diagnoses. In contrast to the significant differences found between schizophrenia and DID groups by Dorahy et al (2009) and Laddis and Dell (2012), Honig et al (1998) found no significant differences between schizophrenia and DID groups regarding voice characteristics. A potential explanation for the differing results found between studies may be that small sample sizes were used, consequently limiting the statistical power in order to detect differences between variables.…”
Section: Dissociative Identity Disorder (Did)contrasting
confidence: 82%
“…Similarly, Laddis and Dell (2012) found no significant correlation between trauma exposure (TEQ score) and dissociation (MID score)…”
Section: Associations With Measures Of Traumamentioning
confidence: 87%
See 2 more Smart Citations
“…It seems the so-called positive symptoms of schizophrenia, borderline symptoms and the pathological manifestations of dissociation may discriminate those with severe dissociative disorders from those with chronic/dissociative PTSD or less severe dissociative disorders. Empirical work has noted the high prevalence of Schneiderian, borderline and pathological dissociative symptoms in severe dissociative disorders (Ellason et al, 1996;Fink and Golinkoff, 1990;Laddis and Dell, 2012;Ross et al, 1990), but few studies have used child abuse-related chronic PTSD comparison groups whose abuse severity overall was similar to those of the DD group. Interestingly, a study of the same data set examining abuse and neglect more closely found that the DD and Chr-PTSD samples were similar on all forms of abuse severity except sexual abuse, where the DD group was higher (Dorahy et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%